2011
DOI: 10.1021/jm201156x
|View full text |Cite
|
Sign up to set email alerts
|

NHC Gold Halide Complexes Derived from 4,5-Diarylimidazoles: Synthesis, Structural Analysis, and Pharmacological Investigations as Potential Antitumor Agents

Abstract: A series of novel neutral NHC gold halide complexes derived from 4,5-diarylimidazoles were synthesized, characterized, and analyzed for biological effects. High growth inhibitory effects in MCF-7 and MDA-MB 231 breast cancer as well as HT-29 colon cancer cell lines depended on the presence of the C4,C5-standing aromatic rings. Methoxy groups at these rings did not change the growth inhibitory properties, while F-substituents in the ortho-position (5d) increased the activity in MCF-7 and MDA-MB 231 cells. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 59 publications
10
139
0
Order By: Relevance
“…As Au(III) and Pt(II) are isoelectronic and they have square planer geometry one expected it would be nice choice of Au(III) as alternative as many cases cisplatin is resistive towards a series cancer cell lines. Guest's group has shown that Au(III)eNHC complexes of 4,5-diarylimidazolidene are very potent against MCF-7, HT-29, HCT-116 and HEP-G2 Cells [42], But it is also observed in many cases Au(III)eNHC are less potent than corresponding Au(I)e NHC complexes as Au(III) finally reduced to Au(I) under physiological condition [13]. Present Au(III) compound, 4 is lees potent than reported Au(III)eNHC by our group; probably bulky naphthyl group prohibit to enter into the cell which is the reason of lower potency.…”
Section: Com-plex Experimental Theoreticalmentioning
confidence: 99%
“…As Au(III) and Pt(II) are isoelectronic and they have square planer geometry one expected it would be nice choice of Au(III) as alternative as many cases cisplatin is resistive towards a series cancer cell lines. Guest's group has shown that Au(III)eNHC complexes of 4,5-diarylimidazolidene are very potent against MCF-7, HT-29, HCT-116 and HEP-G2 Cells [42], But it is also observed in many cases Au(III)eNHC are less potent than corresponding Au(I)e NHC complexes as Au(III) finally reduced to Au(I) under physiological condition [13]. Present Au(III) compound, 4 is lees potent than reported Au(III)eNHC by our group; probably bulky naphthyl group prohibit to enter into the cell which is the reason of lower potency.…”
Section: Com-plex Experimental Theoreticalmentioning
confidence: 99%
“…[13][14][15] NHCs have also been attractive key components in the field of medicinal chemistry. 16,17 Notably, NHCs are well known for stabilizing ligands of virtually every transition metal with strong electron donation from nitrogen atoms to the carbene-metal bond. 18,19 These interesting compounds predominantly enrich the organometallic chemistry as the ligands for stabilizing the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the development of more stable gold complexes with fine tuning of their ligands is of particular interest [11]. With the NHC ligands showing donor properties similar to those of phosphines, the ease of systemic modifications of the NHC substituents has made them attractive ligands for the development of gold complexes as potential apoptotic agents against cancer cells [12]. It may be mentioned that cancer cell death through apoptosis is a desired goal.…”
Section: Introductionmentioning
confidence: 99%